2023
DOI: 10.1021/jacs.3c03608
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P460 Cofactor Maturation Proceeds via Peroxide-Dependent Post-translational Modification

Abstract: Cytochrome P460s are heme enzymes that oxidize hydroxylamine to nitrous oxide. They bear specialized “heme P460” cofactors that are cross-linked to their host polypeptides by a post-translationally modified lysine residue. Wild-type N. europaea cytochrome P460 may be isolated as a cross-link-deficient proenzyme following anaerobic overexpression in E. coli. When treated with peroxide, this proenzyme undergoes maturation to active enzyme with spectroscopic and catalytic properties that match wild-type cyt P460.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…We previously showed that cross-link formation in either the WT proenzyme or an Arg44Ala mutant is driven by peroxide, which motivated us to determine whether the Phe41Ala mutant could undergo the same maturation process. 20 Indeed, reaction of 10 μM Phe41Ala cyt P460 with 3 equivalents of Li 2 O 2 (30 μM) resulted in the immediate decay of the 403 nm Soret and isosbestic conversion to a broad Soret centered at 436 nm consistent with a cross-linked ferryl-type compound II product observed previously for WT cyt P460 ( Fig. 4 ).…”
Section: Resultssupporting
confidence: 72%
See 4 more Smart Citations
“…We previously showed that cross-link formation in either the WT proenzyme or an Arg44Ala mutant is driven by peroxide, which motivated us to determine whether the Phe41Ala mutant could undergo the same maturation process. 20 Indeed, reaction of 10 μM Phe41Ala cyt P460 with 3 equivalents of Li 2 O 2 (30 μM) resulted in the immediate decay of the 403 nm Soret and isosbestic conversion to a broad Soret centered at 436 nm consistent with a cross-linked ferryl-type compound II product observed previously for WT cyt P460 ( Fig. 4 ).…”
Section: Resultssupporting
confidence: 72%
“…S2 † ), which had g -values of 6.02, 5.54, and 1.99 (Table S2 † ). 20 The second component was a more rhombic signal with an E / D = 0.03 and g -values of 6.54, 5.05, and 1.97, consistent with those of CL WT cyt P460. 9 The resonance Raman spectrum obtained with laser excitation at 405 nm was also consistent with previously characterized CLD mutants with an oxidation state marker band ( ν 4 ) at 1367 cm −1 and spin state marker band ( ν 3 ) at 1485 cm −1 (Table S3 † ).…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations